2023
DOI: 10.1097/rct.0000000000001415
|View full text |Cite
|
Sign up to set email alerts
|

Osseous-Tissue Tumor Reporting and Data System With Diffusion-Weighted Imaging of Bone Tumors—An Interreader Analysis and Whether It Adds Incremental Value on Tumor Grading Over Conventional Magnetic Resonance Imaging

Abstract: The aim of the study is to determine whether the use of diffusion-weighted imaging (DWI) provides incremental increase in performance in the osseous-tissue tumor reporting and data system (OT-RADS) with the hypothesis that use of DWI improves interreader agreement and diagnostic accuracy. Methods:In this multireader cross-sectional validation study, multiple musculoskeletal radiologists reviewed osseous tumors with DW images and apparent diffusion coefficient maps. Four blinded readers categorized each lesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The authors also conducted a similar study to assess the added diagnostic value of incorporating the DWI sequences into the OT-RADS. They concluded that the addition of DWI does not significantly enhance the diagnostic performance of OT-RADS [10].…”
Section: Osseous Tumor Reporting and Data System (Ot-rads)mentioning
confidence: 99%
“…The authors also conducted a similar study to assess the added diagnostic value of incorporating the DWI sequences into the OT-RADS. They concluded that the addition of DWI does not significantly enhance the diagnostic performance of OT-RADS [10].…”
Section: Osseous Tumor Reporting and Data System (Ot-rads)mentioning
confidence: 99%